Gestión del área de realización audiovisual de media networks latin american - Massa Olazábal, Alfonso Fernando (2021)
Audiovisual production is the process of creating an audiovisual product. This process transcends the project development, from the arising of the idea to the point when it reaches the audience. It encompasses technical aspects, such as choosing the cameras, audio equipment, resources for the setting, etc.; as well as the artistic aspects related to the audiovisual narrative, such as choosing the planes, music, atmosphere, wardrobe, and talent direction. Therefore, the audiovisual producer’s profile is that of a professional who is able to perform in tow roles that are usually perceived as opposing or antagonistic: the project manager and the artist. I believe both mi academic background and 18- year professional experience have allowed me to become an audiovisual producer specialized in the direction of audiovisual projects, focusing in the communication goals in order to create a product that balances audiovisual quality and resource optimization. I also manage and organize human teams for the production of multiple audiovisual contents and formats.